Differences in universal health coverage and governments' COVID-19 communication: A global comparative analysis - Weder, Franzisca; Courtois, Cedric (Frontiers in Communication, 2022)
The incorporation of widespread, high-quality prevention campaigns and health communication is an integral part of universally accessible healthcare systems. Importantly, in the context of COVID-19, effective public health communication has proven a key mitigating factor. Considering the global differences in countries' universal health coverage, the scope of this study is to formally compare how governments around the globe communicated at the onset of the pandemic. Health communication research has traditionally focused mainly on practices within particular systems, whereas the global scale of the pandemic provides the opportunity to widen the analysis to differences between systems. In this study, 66,167 tweets from 324 government leaders, health ministers and ministries from 139 countries were analyzed using computational content analysis (i.e., topic modeling). The results show that as the pandemic initially intensified, countries with lower degrees of access to universal healthcare were inclined to communicate differently than countries with widely accessible and strongly equipped health care systems. More specifically, the former compensated their structural vulnerabilities and lack of tradition in health communication by highlighting individual and community responsibilities over government measures. In contrast, the latter countries emphasized the aptness of their healthcare systems and infrastructures.